2013
DOI: 10.1002/cssc.201300915
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Interfacial Electron Dynamics in Highly Efficient Zn2SnO4‐Based Dye‐Sensitized Solar Cells

Abstract: Among ternary oxides, Zn2 SnO4 (ZSO) is considered for dye-sensitized solar cells (DSSCs) because of its wide bandgap, high optical transmittance, and high electrical conductivity. However, ZSO-based DSSCs have a poor performance record owing largely to the absence of systematic efforts to enhance their performance. Herein, general strategies are proposed to improve the performance of ZSO-based DSSCs involving interfacial engineering/modification of the photoanode. A conformal ZSO thin film (blocking layer) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…14 ). In addition, it has a wide optical band gap of 3.8 eV and a relatively low refractive index of ∼2.0 in the visible spectrum 15 16 . Furthermore, the conduction band edge position that is similar to that of TiO 2 and ZnO makes it an excellent photoelectrode in emerging solar cell technologies, such as PSC, dye sensitized solar cell (DSSC) and organic photovoltaic (OPV) 17 18 19 .…”
mentioning
confidence: 99%
“…14 ). In addition, it has a wide optical band gap of 3.8 eV and a relatively low refractive index of ∼2.0 in the visible spectrum 15 16 . Furthermore, the conduction band edge position that is similar to that of TiO 2 and ZnO makes it an excellent photoelectrode in emerging solar cell technologies, such as PSC, dye sensitized solar cell (DSSC) and organic photovoltaic (OPV) 17 18 19 .…”
mentioning
confidence: 99%
“…On the other hand, there is no substantial reports are available based on ternary metal oxide (TMO) as electron transporting layer (ETL) for PSC. Shin et al reported nano-particulate BaSnO 3 and Zn 2 SnO 4 ternary metal oxides (TMO) for dye sensitized solar cells, and demonstrated 6.2%, 6%, power conversion efficiency (PCE) respectively1920. Moreover, Zn 2 SnO 4 nanoparticles have been used for PSC and demonstrated ~7% PCE21.…”
mentioning
confidence: 99%
“…The increased photocurrent density may be attributed to the effective charge injection from strongly anchored dyes by the equilibrium-shifting action of TEOS, as well as to a downward CBE shift. Moreover, the device showed a better long-term stability than the [101] untreated reference cell. Post-treatment of nanoporous TiO2 films with a solution of TiCl4 has been a very common method for fabricating a nanoporous TiO2 films that serve both as a substrate for the dye and as the electron conductor.…”
Section: Materials Suitable For Surface Treatmentmentioning
confidence: 94%